Professores e professoras que ensinam matemática e seus discursos sobre a metodologia de projetos de aprendizagem e tecnologias digitais - Boreggio, Joyce Carolina Trombini (2024)
The advances in the digital world influence the ways of being in closed conversation networks. Such involvement implies the need to understand the use of active methodologies and digital technologies in cultures that participate in the technological advances that drive the direction of our society. In this sense, the research seeks to understand how a closed network of conversations made up of teachers who teaches mathematics in Basic Education, and who participated in the the continuing education course are structured around training for understanding and planning classes involving the methodology of learning projects using digital technologies? By carrying out a survey on the theme surrounding the research, it is possible to identify initiatives that aim to unveil the teacher’s constitution for the pedagogical use of active methodologies and digital technologies. However, it is clear that this aspect does not run out, considering that we live in a society undergoing constant transformation, and it is important to continue searching for elements capable of making us continue to be capable of forming citizens in the 21st Century. For the development of the research, which is focused on the qualitative research approach, was offered an online course to 40 teachers who teach mathematics in the public education system in the region comprised by the 18th Regional Education of the state of Rio Grande do Sul, which comprises the cities of Rio Grande, São José do Norte, Santa Vitória do Palmar and Chuí. 15 teachers participated in the training and, consequently, in the research. For data collection, a digital questionnaire with three open questions was used as an instrument and the data was analyzed using the collective subject discourse technique. Through discourse analysis, it is clear how the particularities of each person reveal themselves spontaneously in the same way as the approaches to the ways of being in the profession were outlined in the construction of collective discourse that represents the entire collective. The collective discourse were able to highlight the understandings of a group of teachers who teach mathematics about the methodology of learning projects and digital technologies, as well as their potential in an intertwined way. Possibilities and challenges based on the training and infrastructure of education spaces are guiding elements in comprehension about understanding and interests of this studied collectivity.